Co-composting of food waste and swine manure augmenting biochar and salts: Nutrient dynamics, gaseous emissions and microbial activity - Ravindran, Balasubramani; Awasthi, Mukesh Kumar; Karmegam, Natchimuthu; Chang, Soon Woong; Chaudhary, Dhiraj Kumar; Selvam, Ammaiyappan; Nguyen, Dinh Duc; Rahman Milon, Ashequr; Munuswamy-Ramanujam, Ganesh (Bioresource Technology, 2022)
[Display omitted] •Decomposition process is accelerated by biochar through its affluence of carbon.•Biochar amendment reduced the emission of greenhouse gases, CO2 and CH4.•Biochar in swine manure + food waste composting increased the nitrogen conservation.•Biochar addition (6%) and salts to organic wastes eliminate pathogens in compost. The prominent characteristics of the biochar, high porosity, sorption capacity with low density improve the aeration, making it a desirable amendment material for composting process. The composting efficiency was analysed by the impact of rice husk biochar amendment (0, 2, 4, 6, 8 and 10%) in the presence of salts for the co-composting of food waste and swine manure, in composting reactors for 50 days. Results revealed that biochar amendment had improved the degradation rates by microbial activities in comparison with control. The final compost quality was improved by reducing the bulk density (29–53%), C/N ratio (29–57%), gaseous emissions (CO2, CH4, and NH3) and microbial pathogens (Escherichia coli and Salmonella sp.). However, 6% biochar amendment had significant improvement in compost quality, degradation rates and nutritional value which is recommended as the ideal ratio for obtaining mature compost from the feedstock, food waste and swine manure.